A SURVE Y ON THE SOLVABILITYAND SIMPLICITY STATUS OF PERMUTATION GROUPS - M. BELLO; Mathematics; Computer Science Department, Federal University Kashere, Gombe State, Nigeria (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2019)
This paper is a survey for the solvability and simplicity status of a permutation group G whose order is of the form ???????????? , where r is any prime and p is odd prime. The group of this form can be p-group or any group generated by wreath products of two permutation groups depending on the value of r and p. The concept of p groups and wreath products of two permutation groups has been applied to explore the groups of interest and later investigation has been carried out to test them for the above stated status.